Headache and Neuroimmunology: controversies - Domingues, Renan Barros; Teixeira, Antônio Lúcio (Headache Medicine, 2010)
Headaches are prevalent among patients with neuroimmunological disorders of the central nervous system (CNS). Some autoimmune diseases of the CNS are traditionally recognized as headache causes and therefore are included in the International Headache Disorders Classification. In other conditions, such as systemic lupus erythematosus, multiple sclerosis, and Behçet´s disease, it is uncertain whether there is a causal relationship between headache and the immunologic disease. The presence of a headache history in a patient with an autoimmune disorder of the CNS may be only casual since primary headaches are very prevalent in the general population. In the other hand, CNS inflammatory activity associated with these autoimmune diseases may potentially provoke headache and may also exacerbate a preexisting primary headache. In this article we make narrative revision of the literature about this issue, presenting the current evidence of the association of headache and such immunologic disorders, and critically discuss the potential therapeutic implications in the management of headaches in patients with these autoimmune diseases.